Future anxiety and the motives for postponing parenthood: generational time perspective and life satisfaction as mediators - Szcześniak, Małgorzata; Timoszyk-Tomczak, Celina; Łoś, Julia; Grzeczka, Monika (Frontiers in Psychology, 2025)
Research to date has focused largely on the consequences of delayed parenting. However, little is known about the reasons and relevant mechanisms that are involved in people's decisions to delay parenthood. The aim of our study was to verify how anxiety about the future relates to the motives for deferred parenthood and how this relationship is mediated by generational time perspective and life satisfaction. Methods: A total of 203 Polish adults between 18 and 40 years of age participated in the study. All of them were of reproductive age but did not yet have children. Respondents completed the following questionnaires: The Dark Future Scale, The Multidimensional Scale of Motives for Postponing Parenthood, The Generational Time Perspective Questionnaire, and The Riverside Life Satisfaction Scale.The results obtained in the study show that future anxiety correlates significantly and positively with all six motives for postponing parenthood, postponed parenthood overall, and generational affectivity. It is also associated with the generational cognitive perspective at the level of tendency, and negatively with life satisfaction. According to our findings, in all seven models, at least one of the factors mediated the relationship between future anxiety and motives for postponing parenthood/its total score.The current study advances the understanding of how the subjective future time perspective is related to delayed parenthood through generational concern and reduced life satisfaction. Our findings may indicate that despite the importance of sociodemographic variables in postponing parenthood (e.g., lack of housing, financial instability, acquiring 3 knowledge, education, etc.), variables related to personality and time perspective play a very important role in postponing the decision to have a child.